Curriculum and Learning System at Nurul Islam Islamic Boarding School Cianjur - Dera Nugraha; Nurwadjah Ahmas; Andewi Suhartini (STIT Al-Quraniyah Manna, 2021)
Pondok Pesantren is educational institution that still exist in Indonesia today. Nurul Islam is one of them located in Cianjur regency, has a place in the society so far. This study aims to see how the curriculum and learning system are presented to the students. The method used is descriptive qualitative, a method that seeks to raise a complete phenomenon, through in-depth data processing from selected informants. The results showed that the curriculum used was purely based on kitab kuning. The learning system is carried out with sorogan and balagan. Sevice the community, the madrasah / formal islamic school establishment, the sincerity of teachers, and the inculcation of values ​​to honor teachers have proven to make it exist across generations. Keywords: Curriculum, Learning system, Pesantren